Back Cover: Selective Formation and Unusual Reactivity of Tetraarsabicyclo[1.1.0]butane Complexes (Angew. Chem. Int. Ed. 34/2014). Issue 34 (1st July 2014) - Schwarzmaier, Christoph; Timoshkin, Alexey Y.; Balázs, Gábor; Scheer, Manfred
<x xml:space="preserve">Abstract</x> White phosphorus and yellow arsenic can be selectively activated with dimeric metal complexes, as described by M. Scheer et al. in their Communication on page 9077 ff. The resulting P4 and As4 butterfly complexes of iron and chromium are unprecedented. Surprisingly, they dimerize after photolytic activation or even at room temperature to afford the first examples of As8 cuneane complexes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>